Implementation of Hypno English Teaching Assisted by Technology in Learning English - M. Fajru Sidqi; Yohannes Michell Darius Prana Jaya (Universitas Muhammadiyah Semarang, 2018)
English learning is required efficiency to achieve minimum standards of learning as stated in basic competence. The English language curriculum takes 4 hours of lesson in junior high and 2 hours of high school level, whereas the demands of language are both verbal and written communication. The habit of learning is very poor when looking at the time allocation set so it requires a breakthrough in the learning model used by the teacher. Language habituation focuses first from the realm of concentration to practice in stages according to the condition of learning materials; the model used is with hypno English teaching as a form of development of hypnoteaching that has been first popular, the specificity of this model because it is devoted to learning English with focus absorption of materials and communication skills. The research method used is development; namely by developing a grip hypno-teaching transformed into hypno English teaching with a touch of technology in accordance with the prototype of this learning model. The outcome of this research is the development of hypno-teaching technology-aided model that can be applied to all the characters of learners.